The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3171/2015.4.spine141143
|View full text |Cite
|
Sign up to set email alerts
|

Faster extubation time with more stable hemodynamics during extubation and shorter total surgical suite time after propofol-based total intravenous anesthesia compared with desflurane anesthesia in lengthy lumbar spine surgery

Abstract: OBJECT Anesthesia techniques can contribute to the reduction of anesthesia-controlled time and may therefore improve operating room efficiency. However, little is known about the difference in anesthesia-controlled time between propofol-based total intravenous anesthesia (TIVA) and desflurane (DES) anesthesia techniques for prolonged lumbar spine surgery under general anesthesia. METHODS A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Previous studies demonstrated that ACT, including exit from the OR after extubation, total OR time, and PACU time, may be affected by extubation time [7, 13, 14]. In other words, similar extubation time may contribute to equivalent PACU time, exit from OR after extubation, and total OR time in the same type of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that ACT, including exit from the OR after extubation, total OR time, and PACU time, may be affected by extubation time [7, 13, 14]. In other words, similar extubation time may contribute to equivalent PACU time, exit from OR after extubation, and total OR time in the same type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In spine surgery, we discontinued DES or propofol at the end of the operation or at the last three stitches of surgery. After turning the patients to a supine position, the lungs were ventilated with 100% oxygen at a fresh gas flow of 6 L/min [11,14]. In addition, we used closed-circuit anesthesia in the DES patients, which would prolong neuromuscular blockade and contribute to delay emergence [47].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, the authors also found better hemodynamic control with propofol as compared with desflurane at extubation in lumbar surgery patients. 17 In our study, patients having tachycardia (26/30 versus 16/30) and bradycardia (9/30 versus 2/30) were more in the desflurane group compared with the propofol group. In an earlier study, HR was found significantly higher with desflurane as compared with sevoflurane and propofol.…”
Section: Discussionmentioning
confidence: 46%
“…These findings were consistent with several of our previous studies showing that general anesthesia using TCI system with propofol could achieve faster extubation than using DES in different surgeries. [ 5 – 9 , 12 , 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…As a retrospective study, the cases we collected were performed under routine clinical protocol, using 6 L/min of fresh gas flow during emergence. In our serial retrospective studies [ 5 8 , 13 15 ] TIVA delivered by TCI system has the advantage in predicting the propofol effect-site concentration at return of consciousness. [ 16 , 32 34 ] Moreover, TCI system could calculate the time required to reach such concentration, and therefore improve the OR efficiency.…”
Section: Discussionmentioning
confidence: 99%